PENGEMBANGAN LKPD MATERI KEANEKARAGAMAN HAYATI BERBASIS MODEL PROBLEM BASED LEARNING KELAS X SMA - Kristina Novita; Yohanes Bare; Mansur S (Universitas Cokroaminoto Palopo, 2022)
Learning development is one of the innovations in improving student achievement, one of which is by adopting the Problem Based Learning model combined with the Student Worksheet (LKPD). This model of developments is adapted to the material on biodiversity. The purpose of this study is to validate and analyze the feasibility of the resulting LKPD. The development research method adopted is the research and development of the Four-D (4D) model. The results of the LKPD research were valid by material experts (80%), media experts (87.78%), and linguists (81.25%) with a very valid category and obtained a very decent feasibility score. The LKPD developed is expected to be a solution to classroom learning.